YIELD IN SAWN WOOD AND RESIDUE UTILIZATION OF Qualea paraensis DUCKE AND Erisma uncinatum WARM - Stragliotto, Michelly Casagrande; Freitas, Jefferson Melo; Oliveira, Aylson Costa; Pereira, Barbara Luísa Corradi (Floresta, 2019)
The study was developed in Nova Maringá - MT. The objectives of this work were to evaluate the sawn timber yield, the use of wood residues and the quantification of products for the species Qualea paraensis (cambará) and Erisma uncinatum (cedrinho) in three diametric classes: Class A - 40.0 to 49.9 cm; Class B - 50.0 to 59.9 cm; Class C - 60.0 to 69.9 cm. Four replicates per class were evaluated, totaling 12 logs per species of varied lengths. The sawn timber yield did not show a statistical difference between diametric classes for both species. Average yield for Qualea paraensis was equal to 43.97% and for Erisma uncinatum, 42.05%. The residues use increased the total yield in 4.40% and 6.52% for Qualea paraensis and Erisma uncinatum, respectively. For Erisma uncinatum, the sawed products with the highest production were the board in the primary unfolding and the short board in the residues use. As for Qualea paraensis, there was more production of rafters and short battens in the same processes.